Hormone-dependence of sarin lethality in rats: sex differences and stage of the estrous cycle - Smith, Carl D. (Toxicol Appl Pharmacol, 2015)
Chemical warfare nerve agents (CWNAs) are highly toxic compounds that cause a cascade of symptoms and death, if exposed casualties are left untreated. Numerous rodent models have investigated the toxicity and mechanisms of toxicity of CWNAs, but most are limited to male subjects. Given the profound physiological effects of circulating gonadal hormones in female rodents, it is possible that the daily cyclical fluctuations of these hormones affect females’ sensitivity to the lethal effects of CWNAs, and previous reports that included female subjects did not control for the stage of the hormonal cycle. The aim of the current study was to determine the 24-hour median lethal dose (LD(50)) of the CWNA sarin in male, ovariectomized (OVEX) female, and female rats during different stages of the estrous cycle (diestrus, proestrus, and estrus). Additionally, baseline activity levels of plasma acetylcholinesterase, butyrylcholinesterase, and carboxylesterase were measured to determine differences among the groups. Results indicated that females in proestrus had a significantly higher LD(50) of sarin compared to OVEX and estrous females. Although some sex differences were observed in the activity levels of plasma esterases, they were not consistent and likely not large enough to significantly affect the LD(50)s. These results suggest that hormonal cyclicity can influence the outcome of CWNA-related studies using female rodents, and that this variability can be minimized by controlling for the stage of the cycle. Additional research is necessary to determine the precise mechanism of the observed differences because it is unlikely to be solely explained by plasma esterase activity.